Global Methylation and Hydroxymethylation in DNA from Blood and Saliva in Healthy Volunteers. (18th May 2015) - Godderis, Lode; Schouteden, Caroline; Tabish, Ali; Poels, Katrien; Hoet, Peter; Baccarelli, Andrea A.; Van Landuyt, Kirsten
Abstract : Aims . We describe a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method to quantify and compare simultaneously global methylation and hydroxymethylation in human DNA of different tissues. Materials and Methods . Blood and saliva DNA from fourteen volunteers was processed for epigenetic endpoints using LC-MS/MS and PCR-pyrosequencing technology. Results . Global DNA methylation was significantly lower in saliva (mean 4.61% ± 0.80%), compared to blood samples (5.70% ± 0.22%). In contrast, saliva (0.036% ± 0.011%) revealed significantly higher hydroxymethylation compared to blood samples (mean 0.027% ± 0.004%). Whereas we did not find significant correlations for both epigenetic measures between the tissues, a significant association was observed between global methylation and global hydroxymethylation in saliva DNA. Neither LINE-1 nor Alu elements of blood and saliva correlated, nor were they correlated with the DNA hydroxymethylation of blood or saliva, respectively. Conclusion . Global DNA methylation and hydroxymethylation of cytosine can be quantified simultaneously by LC-MS/MS. Saliva DNA cannot be considered as a surrogate for blood DNA to study epigenetic endpoints.